(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
Which resources and capabilities ease the change to become a Technology-Based and Highly Innovative Firm –TB&InnF–, focused in the creation of value to market? We analyse this question using a novel data panel assembled for 326 Spanish industrial firms, along the period 1984-2012. Our findings show the probability of becoming a TB&InnF growths when firms are able to accumulate a high endowment of knowledge and technological capabilities, and a managerial team with: experience, strong power position and previous technical and managerial education. Results also indicate the CEO´s educational profile in management is preferable to a pure technical profile, because this complements firm´s knowledge and technological capabilities and enables the transformation of a scientific or technological project into a successful entrepreneurial innovation, which creates new value to market. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.